The inverse association of elevated serum bilirubin levels with subclinical carotid atherosclerosis - Vítek, Libor; Novotný, Ladislav; Sperl, Michal; Holaj, Robert; Spácil, Jirí (Cerebrovascular diseases (Basel, Switzerland), 2006)
BACKGROUND: Serum bilirubin is negatively associated with the development of coronary heart disease. In the present study, we have focused on the analysis of intima-media thickness (IMT) of the common carotid artery in hyper- and normobilirubinemic subjects. METHODS: The study was performed on 111 men without manifested atherosclerosis. In all subjects, complete biochemical tests were determined along with the examination of IMT by carotid ultrasound. RESULTS: The mean IMT in hyperbilirubinemic subjects as compared with controls was substantially lower (p=0.017), and hyperbilirubinemic men also had very low age-adjusted prevalence odds ratios for having IMT above the 50th percentiles of controls, even after adjustment for selected vascular risk factors (p=0.034). CONCLUSIONS: In the present study, we demonstrate the inverse relationship between serum bilirubin and IMT in healthy men.
Keywords: dospělí; Bilirubin; Carotid Artery, Common; jaterní testy; biologické markery; tunica intima; Age Factors; Biomarkers; ultrasonografie; Adult; Tunica Media; věkové faktory; lidé; Ultrasonography; studie případů a kontrol; Humans; Tunica Intima; tunica media; Male; Case-Control Studies; Aged; arteria carotis communis; bilirubin; lidé středního věku; Liver Function Tests; senioři; Gilbertova nemoc; mužské pohlaví; Middle Aged; Gilbert Disease